THE ROLE OF IMMUNOSTIMULANTS IN INCREASING THE RESISTANCE OF COTTON TO GUMMOSIS (Web of Teachers: Inderscience Research, 2024)
In this article, information about the role of the immunostimulants Fitovak and Zerox on the gummosis disease of the cotton plant. The obtained results showed that Zerox immunostimulant played an important role in increasing the resistance of cotton to gummosis compared to Fitovak immunostimulant.